Metacognitive level of chemistry students in the chemistry department of Universitas Negeri Surabaya - Hidayah, Rusly; Habiddin, Habiddin; Dasna, I Wayan; Parlan, Parlan; Nazriati, Nazriati (Eclética Química, 2026)
This study intends to describe students’ metacognitive skills about their study plans and the length of the learning experience at the Chemistry Department, Universitas Negeri Surabaya. The study involved 200 students from 2 study programs (chemistry education and chemistry). According to this study, students’ metacognitive skills in both programs were more than adequate. When the ability was described in light of their study programs, students from the two study programs showed a slight discrepancy in that capacity. The same phenomenon was observed in the length of their university studies, where all four batches of students (first, second, third, and fourth) showed the considerable differences in the metacognitive abilities of chemistry students between classes with a significance value of 0.003 (<0.05). The interesting finding demonstrated that the first-year students showed the highest metacognitive scores (77.20), while the fourth-year students had the lowest (75.26).